Aqueous phase reforming of birch and pine hemicellulose hydrolysates. (March 2022) - Aho, Atte; Alvear, Matias; Ahola, Juha; Kangas, Jani; Tanskanen, Juha; Simakova, Irina; Santos, José Luis; Eränen, Kari; Salmi, Tapio; Murzin, Dmitry Yu.; Grénman, Henrik
Highlights: Aqueous phase reforming of real hemicellulose hydrolysates was performed. The best results were obtain with a tailored bimetallic Pd-Pt/sibunit catalyst. Complete conversion was achieved for C5 and C6 sugars and formic acid. Abstract: The current work focuses on studying the aqueous phase reforming (APR) of pine and birch hydrolysate obtained from waste wood by using organic acids available from biorefineries. Processing of representative synthetic mixtures was utilized in the work in order to support data interpretation related to the influence of different chemical compound and processing parameters on the APR of the actual hydrolysates. It was shown, that hydrogenation of the hydrolysates prior to APR was not feasible in the presence of formic acid, which ruled out one potential processing route. However, it was successfully demonstrated that birch and pine hydrolysates could be directly processed obtaining close to full conversion. The best results were obtained with tailored bimetallic Pd-Pt/sibunit catalyst in a trickle bed reactor system in the temperature range 175 °C–225 °C.